HIGHLY SENSITIVE AND RAPID EVALUATION OF PYRIDOSTIGMINE IMPURITY B IN HUMAN PLASMA BY LIQUID CHROMATOGRAPHY COUPLED WITH TANDEM MASS SPECTROMETER AFTER ADMINISTRATION OF PYRIDOSTIGMINE TO HEALTHY VOLUNTEERS IN A PHARMACOKINETIC STUDY - Puram, Sambasiva Rao; Batheja, Raman; Nithya, G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Objective of this work is to evaluate the levels in plasma of pyridostigmine impurity B (metabolite of pyridostigmine) in humans after administration of pyridostigmine formulations. Methods: Plasma concentrations of pyridostigmine impurity B were estimated using by liquid chromatography coupled with electron spray ionization triple quad mass spectrometer technique, lamivudine is used as an internal standard. Multiple reaction at 109.9/95.2 (pyridostigmine impurity B) and 230.2/112.2 (lamivudine) were monitored. Chromatography was optimized using acetonitrile: Buffer (10 millimolar ammonium acetate) (85:15) on an Inertsil C18, 150 mmÃ—4.6 mm, 5 Î¼ analytical column. Linear Calibration curve set between 1.434 ng/ml and 39.637 ng/ml. Sample extraction was conducted using solid phase extraction method using mixed mode cation exchange cartridges. The method was developed on API 4000. Results: Method was developed, tested for system suitability, carryover, selectivity, matrix effect, intra-inter precision and accuracy, recovery, linearity, and various stabilities in aqueous as well as plasma as matrix. The method was validated for all the above validation parameters mentioned as per European medical agency guideline on method validation. Conclusions: The method is successfully applied to analyze 1890 subject samples after administration of pyridostigmine 180 mg as per Independent Ethics Committee approved protocol. Incurred sample reanalysis was revealed a great reproducibility of method. Statistical analysis was also conducted to compare test formulation with innovator formulation. Test formulation concentrations of pyridostigmine impurity B are similar to those obtained from innovator formulation.